The value of cardiac markers in predicting the hospital mortality of ischemic stroke patients - Gurger, Mehtap; Bozdemir, Mehmet Nuri; Yildiz, Mustafa; Gurger, Murat; Ozden, Mehmet; Bozgeyik, Zulkif; Dagli, Mustafa Necati (Wolters Kluwer Medknow Publications, 2008)
Objectives: Stroke is the third leading cause of the deaths after heart diseases and cancer which also resulting with neurological disability. The mortality and morbidity secondary to stroke can be reduced by the early diagnosis and treatment of these patients in emergency department (ED). There may be an increase in D-dimer and cardiac markers in the ischemic stroke and this increase is related to adverse outcome. The aim of this study was to determine the validity of D-dimer and cardiac markers in predicting the in-hospital mortality in ischemic stroke patients. Materials and Methods: This prospective study was performed in an ED of a university hospital with the patients diagnosed to have ischemic stroke between October 2006 and March 2007. D-dimer, creatine kinasemyocardial band (CK-MB), Troponine-I and myoglobin levels of the study patients during the admission were studied and the relation between them and mortality was evaluated. Results: A total of 100 patients were included into the study and 53% of them were male. 59% of the patients had hypertension, 42% atherosclerosis, 33% ischemic cardiac disease, 21% diabetes mellitus, 20% atrial fibrillation, 6% cerebrovascular diseases and 4% had a history of trans-ischemic attack. Thirty four (34%) patients died in the hospital during the study period. D-dimer (2510.21 +/- 327.16 vs 1283.85 +/- 174.23; p=0.000), CK-MB9.51 +/- 3.01 vs 4.32 +/- 0.89; p=0.04) and myoglobin (238.87 +/- 31.13 vs 114.42 +/- 15.23; p=0.00) levels were significantly higher in the mortality group. Tn-I levels were high in four patients. And the patients who died had higher Tn-I levels (1.33 +/- 0.91 vs 0.12 +/- 0.56), however this difference did not reach to a statistical significance (p=0.069). Furthermore, the initial Glasgow Coma Scale score were significantly lower in the mortality group (median: 12 vs 15; p=0.000). Conclusion: D-dimer, myoglobin, CK-MB and the low GCS scores are related to in-hospital mortality in ischemic stroke patients. Further studies with larger sample sizes are needed in order to reveal the validity of Tn-I in ischemic stroke patients to predict mortality.
Keywords: CK-MB; D-dimer; ischemic stroke; myoglobin; mortality; troponine